Penerapan Pembelajaran Luar Kelas di SD Muhammadiyah 1 Surakarta - Dienti, Lulu Sania; Zainuddin, Almuntaqo (Universitas Nahdlatul Ulama Blitar, 2025)
Learners feel bored with learning that is limited to the classroom due to the lack of variety in scenery and the lack of utilization of other learning resources by educators. The purpose of this research is to identify effective strategies in increasing learners' engagement and enriching their learning experience outside the classroom. The research method used was qualitative with the research design using ethnography. The research was conducted through interviews with principals and teachers, then through observation or direct observation and document research. The results of this study show that there are different opinions regarding the effectiveness of out-of-class learning. Although there are differences, basically out-of-class learning can be said to be effective if it is commensurate with the benefits felt by teachers, students, and students. Support provided by SD Muhammadiyah 1 Surakarta is in the form of policy support and facility support. This support is useful for the success of the out-of-class learning form. These forms are 1) Hizbul Wathan Camp, 2) Pesantren Kilat, 3) Visit to Batik Village, 4) Expedition to the Press Monument, 5) Outbound, and 6) Healthy Walk. Although out-of-class learning at SD Muhammadiyah 1 Surakarta is already quite good in its implementation, it still experiences obstacles in its implementation, namely in making proposals, and also time management.